Metode Marketing Mix Dan Analisis SWOT Dalam Penyusunan Strategi Bersaing Pada IKM Keripik Tempe Ayudy - wahyu maulana (Jurnal Perilaku dan Strategi Bisnis, 2020)
Medium small industry (IKM) is one of the real sectors which is a favorite of the public to compete in producing maximum profits. This sector is also a strong foundation for regional governments in developing an independent regional economy. This is the reason for the many SMIs that have sprung up and are dominated by millennials. The purpose of this study was to determine the competitive strategy using the marketing mix method and SWOT analysis on one of the tempe chips SMIs. This type of qualitative research and direct interviews are things that are used in this study. The results showed that the position of IKM Ayudy was in the quadrant I in the SWOT analysis where the right strategy to compete was to use an aggressive strategy. Ayudy IKM will take advantage of open business opportunities by focusing on the strength of its products. The competitive strategy is divided into marketing mix where its application includes a product strategy by doing innovative products, this is considered appropriate because it is to overcome boredom in consumers so that consumers remain comfortable with the product from the IKM Ayudy; pricing strategy is done by implementing wholesale prices, this is intended to facilitate sales quickly; location strategy by opening sales outlets directly aimed at consumers especially those located far from production houses; and of course promotional strategies through social media that make products more known and have an impact on increasing sales